2006
DOI: 10.1152/ajpendo.00462.2005
|View full text |Cite
|
Sign up to set email alerts
|

Leucine in food mediates some of the postprandial rise in plasma leptin concentrations

Abstract: In vitro, leptin secretion is regulated at the level of mRNA translation by the rapamycin-sensitive mammalian target of rapamycin (mTOR) and its agonist leucine (Leu). Studies were conducted on meal-trained rats to evaluate the potential physiological relevance of these in vitro findings and the role of Leu in affecting rises in plasma leptin observed after a meal. In the first study, we correlated changes in plasma insulin and Leu to mTOR-signaling pathway activation and plasma leptin at different times durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 51 publications
3
83
1
5
Order By: Relevance
“…Several factors make leucine an ideal direct nutrient signal to the brain. First, in contrast to plasma glucose and triglyceride concentrations, which do not change appreciably with feeding, leucine concentrations increased severalfold in circulation during a meal (39). Second, leucine regulates the mTOR-signaling pathway in neurons, in vivo (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors make leucine an ideal direct nutrient signal to the brain. First, in contrast to plasma glucose and triglyceride concentrations, which do not change appreciably with feeding, leucine concentrations increased severalfold in circulation during a meal (39). Second, leucine regulates the mTOR-signaling pathway in neurons, in vivo (40).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of BCAAs, particularly leucine, elicits a rise in leptin after 3 h, as shown by Lynch et al (47). This group also showed that norleucine, which does not increase serum insulin, also increases leptin, providing evidence that BCAA increase leptin translation via activation of mTOR (47). Whether amino acids and insulin effects on leptin translation are additive and which factor dominates in vivo will require further research.…”
Section: Nutrients May Signal Alterations In Leptin Productionmentioning
confidence: 97%
“…Increasing mTORC1 activity by overexpression of Rheb or dominant negative AMPK increases leptin translation, and this does not require the presence of leptin 5Ј-UTR (14). In the physiological context, independent of their metabolism into glycolytic substrate or TCA cycle intermediates, amino acids can increase leptin within 2-4 h by acting as signaling molecules activating mTOR (47,48,66). However, the downstream events through which activation of mTOR leads to a specific increase in relative rates of leptin biosynthesis, over and above a small increase in general protein synthesis, remain to be determined.…”
Section: Signaling Pathways Involved In Insulin and Amino Acid-stimulmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Moreover, several nutrient sensing mediators that activate mTOR in adipose tissue, including insulin, leucine and UDP-N-acetylglucosamine, also induce leptin synthesis. 23,[47][48][49] Could these pathways provide positive feedback for leptin action on adipocytes (Fig. 1)?…”
Section: Leptin Activates the Mtor Pathwaymentioning
confidence: 99%